2005
DOI: 10.1021/ja0535918
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Syntheses of (−)-Jorumycin, (−)-Renieramycin G, 3-epi-Jorumycin, and 3-epi-Renieramycin G

Abstract: The total synthesis of (-)-jorumycin (1) and (-)-renieramycin G (2) has been accomplished in 25 and 23 steps, respectively, from 5-benzyloxy-2,4-dimethoxy-3-methyl-benzyl alcohol. The synthesis features a substrate-tunable stereoselective intramolecular Pictet-Spengler-type reaction for the construction of the key pentacyclic core of both targets, bearing either the natural configuration or the epimeric configuration at C-3. With access to a C-3 epi-pentacyclic framework, 3-epi-jorumycin (32) and 3-epi-reniera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 20 publications
1
68
0
Order By: Relevance
“…1 Recently, we reported the asymmetric total syntheses of (−)-jorumycin (1) and (−)-renieramycin G (2). 6 However, en route to 1 and 2, a serendipitous discovery afforded a method to efficiently and selectively access two related natural product analogues, 3-epijorumycin (3) and 3-epi-renieramycin G (4). Preliminary biological evaluation of 3-epijorumycin (3), in addition to relevant synthetic intermediates, revealed low micromolar growth inhibition profiles for all compounds tested in the context of two human cancer cell lines (HCT-116 and A549).…”
mentioning
confidence: 99%
“…1 Recently, we reported the asymmetric total syntheses of (−)-jorumycin (1) and (−)-renieramycin G (2). 6 However, en route to 1 and 2, a serendipitous discovery afforded a method to efficiently and selectively access two related natural product analogues, 3-epijorumycin (3) and 3-epi-renieramycin G (4). Preliminary biological evaluation of 3-epijorumycin (3), in addition to relevant synthetic intermediates, revealed low micromolar growth inhibition profiles for all compounds tested in the context of two human cancer cell lines (HCT-116 and A549).…”
mentioning
confidence: 99%
“…Piers reported that (trimethylstannyl)copper(I) dimethylsulfide complex was relatively unreactive towards α,β-unsaturated carbonyl compounds. 9 When a more reactive species [Me 3 SnCuCN]Li 10 was used in place of Me 3 SnCu·SMe 2 for this reaction we observed that the yield was dramatically improved. When 5a was added to [Me 3 SnCuCN]Li in dry THF at −78 °C, compound 6 and the corresponding Z-isomer were produced in a nearly 1:1 ratio with no recovery of starting material.…”
Section: Resultsmentioning
confidence: 94%
“…The addition of compound 5a to solution of Bu 3 SnCu·SMe 2 or [Bu 3 SnCuCN] Li 9,10 in THF resulted in no reaction. When 5a was added to Me 3 SnCu·SMe 2 in THF, compound 6 was obtained in 23% yield with 40% recovery of 5a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations